Promosi Penjualan, E-Service Quality, dan Citra Merek sebagai upaya Meningkatkan Pengguna Dompet Digital OVO - Rizki Amalia; Sugeng Rianto (Prodi Sistem Informasi, 2022)
Digital wallets introduce people to practical, safer, and more profitable cashless or non-cash payment methods. This payment method has become increasingly popular since Go-Pay and OVO offer many promos and discounts at many merchants. Based on cnbnindonesia.com, in the independent application category, in 2022 OVO leads monthly active users with 20.8 million, followed by Dana and LinkAja. OVO is in the lead because most people use it to transact on Grab and Tokopedia. Recently, they launched a partnership with Bareksa for OVO Invest, a feature for OVO users to buy mutual funds and monitor their price movements within the OVO mobile application. 96 OVO user respondents were tested using a questionnaire. The results showed that sales promotion, e-service quality and brand image had a positive and significant influence on the decision to use OVO as a digital wallet. Keyword: sales promotion, e-service quality, brand image, and decission